Wave hindcast for the Indian Ocean region covering the period of ARMEX-I (June-August 2002) - SWAIN, J.; DE, CHANCHAL; SINGH, M. K.; VIJAYAKUMAR, D.; VENKITACHALAM, N. R. (MAUSAM, 2005)
Wave hindcast has been carried out for the Indian Ocean (30°-120° E, 30° S - 30° N) region covering ARMEX, PHASE-I observational programme (June-August 2002). The analysed wind fields at six hourly intervals provided by National Centre for Medium Range Weather Forecast (NCMRWF), New Delhi is used to drive the third generation wave model “WAM” (1.5° × 1.5° resolution). The primary objectives of this hindcast, is to provide the sea-state information for the period of ARMEX which would help in research applications and to implement WAM operationally for the Indian Ocean to meet various requirements in future. The model was earlier validated using the Ship Borne Wave Recorder (SBWR) data collected onboard INS Sagardhwani, the visual estimates reported in the Indian Daily Weather Report (IDWR) published by the India Meteorological Department (IMD) and time-series buoy measurements of National Institute of Ocean Technology (NIOT). The model outputs are compared with the available buoy data of NIOT. The comparisons between the hindcast wave parameters and measurements reveal that the model could predict wave heights with errors ranging from ±12% to ±20%.